DESIRE AND RELIGION - Verhack, Ignace (Journal of Dharma, 1997)
In this paper, I wish to show that there is a blind spot in Heidegger's treatment, in Being and Time, concerning the will and the movement of Dasein, and that it blocks the way to an ontology of desire and, hence, to a philosophical openness to religion.